Multiple species‐specific molecular markers using nanofluidic array as a tool to detect prey DNA from carnivore scats. Issue 17 (1st August 2021) - Di Bernardi, Cecilia; Wikenros, Camilla; Hedmark, Eva; Boitani, Luigi; Ciucci, Paolo; Sand, Håkan; Åkesson, Mikael
Abstract: Large carnivore feeding ecology plays a crucial role for management and conservation for predators and their prey. One of the keys to this kind of research is to identify the species composition in the predator diet, for example, prey determination from scat content. DNA‐based methods applied to detect prey in predators' scats are viable alternatives to traditional macroscopic approaches, showing an increased reliability and higher prey detection rate. Here, we developed a molecular method for prey species identification in wolf ( Canis lupus ) scats using multiple species‐specific marker loci on the cytochrome b gene for 18 target species. The final panel consisted of 80 assays, with a minimum of four markers per target species, and that amplified specifically when using a high‐throughput Nanofluidic array technology (Fluidigm Inc.). As a practical example, we applied the method to identify target prey species DNA in 80 wolf scats collected in Sweden. Depending on the number of amplifying markers required to obtain a positive species call in a scat, the success in determining at least one prey species from the scats ranged from 44% to 92%. Although we highlight the need to evaluate the optimal number of markers for sensitive target species detection, the developed method is a fast and cost‐efficient tool for prey identification in wolf scats and it also has the potential to be further developed and applied to other areas and large carnivores as well. Abstract : Large carnivore feeding ecology plays a crucial role for management and conservation for both the predators and their prey, and the identification of species composition in the predator diet is pivotal. We developed a molecular method for the identification of 18 target species in wolf ( Canis lupus ) scats using multiple species‐specific marker loci on the cytochrome b gene, which amplified specifically when using a nanofluidic array technology (Fluidigm Inc.). The developed method is a fast and cost‐efficient tool for prey detection in wolf scats and has the potential to be further developed and applied to other areas and other large carnivores as well.